PENERAPAN PERHITUNGAN PPH 21 ORANG PRIBADI BERDASARKAN PP 58 DAN PMK 168 TAHUN 2023 MENGGUNAKAN MICROSOFT EXCEL PADA CV MUDA RIA - Astuti, Indriani Indah; Satriawan, Indra (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2025)
Based on Minister of Finance Regulation Number 252/PMK.03/2008 and Minister of Finance Regulation Number 168 of 2023, this article discusses the application of PPh Article 21 calculations to permanent employees using Microsoft Excel before and after PP 58/PMK 168 of 2023. The author uses documentation and interviews as well as data sources from books, journals and the internet. The results of interviews and documentation show that CV Muda Ria has problems. CV Muda Ria has not calculated income tax article 21 in accordance with Minister of Finance Regulation Number 252/PMK.03/2008 and Minister of Finance Regulation Number 168 of 2023. As a result, the company does not fulfill its tax obligations to deduct employee salaries from income tax article 21. Based on this problem, the discussion that will be reviewed is regarding the calculation of income tax article 21 based on the Minister of Finance Regulation Number 252/PMK.03/2008 for the 2023 tax year and based on the Minister of Finance Regulation Number 168 of 2023 for the 2024 tax year by using the Microsoft excel application.